Lithium for Fracture Treatment (LiFT): a double-blind randomised control trial protocol - Diane Nam; Phumeena Balasuberamaniam; Katrine Milner; Monica Kunz; Kathak Vachhani; Alex Kiss; Cari Whyne (BMJ Open)
Introduction Fracture healing can fail in up to 10% of cases despite appropriate treatment. While lithium has been the standard treatment for bipolar disorder, it may also have a significant impact to increase bone healing in patients with long bone fractures. To translate this knowledge into clinical practice, a randomised clinical trial (RCT) is proposed.Methods and analysis A multicentre double blind, placebo-controlled RCT is proposed to evaluate the efficacy of lithium to increase the rate and predictability of long bone fracture healing in healthy adults compared to lactose placebo treatment. 160 healthy individuals from 18 to 55 years of age presenting with shaft fractures of the femur, tibia/fibula, humerus or clavicle will be eligible. Fractures will be randomised to placebo (lactose) or treatment (300 mg lithium carbonate) group within 2 weeks of the injury. The primary outcome measure will be radiographic union defined as visible callus bridging on three of the four cortices at the fracture site using a validated radiographic union score. Secondary outcome measures will include functional assessment and pain scoring.Ethics and dissemination Participant confidentiality will be maintained with publication of results. Research Ethics Board Approval: Sunnybrook Research Institute (REB # 356–2016). Health Canada Approval (HC6-24-C201560). Results of the main trial and secondary endpoints will be submitted for publication in a peer-reviewed journal and presented at conferences.Trial registration number NCT02999022.